Queuing studies at ELITE Ebor Selatan toll plaza / Afizan Zolkafli - Zolkafli, Afizan (2004)
This study is to compare the queuing characteristics at the difference tollbooth. ELITE Ebor Selatan is selected as study area. The tollbooth in this toll plaza involved manual, Touch n’ Go and SmartTAG. Both macroscopic and microscopic level of analysis is used in this study. For macroscopic analysis, the arrival data are collected using Hi-Star traffic counters and service data are collected manually. For microscopic analysis, both arrival and service data are collected manually at Section A. The findings indicated that, the queuing characteristics of SmartTAG tollbooth is better than Touch n’ Go and manual tollbooths. From microscopic analysis, it shown that the drivers spend about 4 to 6 minutes to be served in the system.